A Sustainable and Systematic MEDIF System / Norizzati Ibrahim ... [et al.] - Ibrahim, Norizzati; Mat Isa, Che Maznah; Mustaffa, Nur Kamaliah; Ab Rani, Nur Izzati; Ghani, Mohd Khairolden (2021)
Construction projects internationally are one of the main catalysts that contribute to the growth of the Malaysian economy through the implementation of mega infrastructure projects. In this regard, the Malaysian government has taken other initiatives through the establishment of the Construction 4.0 Strategic Plan (2021-2025). The report points out that models for entry decisions into overseas markets have underdeveloped locally and abroad. Therefore, the current study is very important in realizing the Construction 4.0 Strategic Plan (2021-2025) through the development of a sustainable and strategic MEDIF system. MEDIF was formulated to help Malaysian construction firms make more strategic entry decisions to enter the international market based on poor to excellent measurement scale values. The MEDIF system was developed as a result of a survey of 74 managers who have experience handling projects at the international level. The data were analyzed using Rasch Model, SEM model, and also SPSS software to strengthen the structure of the MEDIF system. The MEDIF system has identified the most strategic locations (continents) to conduct construction operations based on scale measurements of 1 to 6. The MEDIF system found that the most strategic entry locations were Europe, followed by the United States, Asia, ASEAN, Africa, and Australia. The joint venture has been identified as the most strategic entry mode to ensure that construction firms can sustain in host countries. Finally, the MEDIF system has identified joint ventures as the most suitable entry mode for new entrants to countries located in Europe.